If it's not what You are looking for type in the equation solver your own equation and let us solve it.
Simplifying 3 + -8y = -1 Solving 3 + -8y = -1 Solving for variable 'y'. Move all terms containing y to the left, all other terms to the right. Add '-3' to each side of the equation. 3 + -3 + -8y = -1 + -3 Combine like terms: 3 + -3 = 0 0 + -8y = -1 + -3 -8y = -1 + -3 Combine like terms: -1 + -3 = -4 -8y = -4 Divide each side by '-8'. y = 0.5 Simplifying y = 0.5
| x-7y+y-3-2x+6z= | | (3x-3y)2+18xy= | | 1.15=(1+x)(1+x)(1+x)(1+x)(1+x)(1+x)(1+x)(1+x)(1+x)(1+x)(1+x)(1+x) | | 4x/3+=2 | | -2x+6=-7x+14 | | 4(3x-2)-5(2-x)= | | 17.01y=6.3 | | 9a-6(a+5)= | | .2*n=48 | | (X/4)+3=5 | | 5p-2=9p-2 | | 14c-6=7c-6 | | 10f+4=3f-59 | | 12x-(x*x)=36 | | 3(2a-3b)-4b(4a-4)= | | Z^2+6z-20=00 | | -6w-45=-9(w+8) | | 9x-5y=12 | | Z^2+6x-16=0 | | 50x^2+15x-2=(5x+2) | | 4p-1=9+17 | | 6x-10=6+10 | | 9q+1=4q-44 | | 2=3c+11 | | 4x+40=12x-102 | | (3/2)+4=5 | | x(8+9)= | | 3x/4-3.2=5.3-2x/3 | | 17b=36+3b | | -3c-32=4c+3 | | 5cos^2x-3=0 | | 50x^2-15x-2=(5x+2) |